2008
DOI: 10.1007/s10570-008-9261-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the production of chain-end groups and methanol from the depolymerization of cellulose during the ageing of paper/oil systems. Part 1: Standard wood kraft insulation

Abstract: Recently, the existence of a relation between the rupture of 1,4-b-glycosidic bonds in the cellulose during thermal-ageing of paper/oil systems and the detection of methanol in the oil has been reported for the first time in this journal (Jalbert et al. 2007). The present study addresses the rate constants of the reaction for standard wood kraft papers, two immersed in inhibited naphthenic oil under air (paper/oil weight-volume ratio of 1:18) and one in non-inhibited paraffinic oil under nitrogen (paper/oil we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 10 publications
4
42
1
Order By: Relevance
“…The activation energy (E a ) for the laser depolymerisation of cellulose is found to be of 56 ± 6 kJ mol -1 . This E a value is lower than the *100 kJ mol -1 value generally reported for the hydrolytic depolymerisation of cellulose (Emsley 1994;Zou et al 1996;Karst and Yang 2007;Gilbert et al 2009). Indeed, even higher E a values (in the 76-148 kJ mol -1 range) have been reported for the degradation of cellulose depending on the degradation temperatures (in the 105-280°C range) and the predominant mechanism involved (oxidative, hydrolytic or pyrolytic) (Emsley 1994).…”
Section: Kineticscontrasting
confidence: 61%
“…The activation energy (E a ) for the laser depolymerisation of cellulose is found to be of 56 ± 6 kJ mol -1 . This E a value is lower than the *100 kJ mol -1 value generally reported for the hydrolytic depolymerisation of cellulose (Emsley 1994;Zou et al 1996;Karst and Yang 2007;Gilbert et al 2009). Indeed, even higher E a values (in the 76-148 kJ mol -1 range) have been reported for the degradation of cellulose depending on the degradation temperatures (in the 105-280°C range) and the predominant mechanism involved (oxidative, hydrolytic or pyrolytic) (Emsley 1994).…”
Section: Kineticscontrasting
confidence: 61%
“…60-210°C (Gilbert et al 2009(Gilbert et al , 2010Jalbert et al 2015). This finding allows accelerated ageing tests to be used at high temperatures to study ageing under normal transformer temperatures, such as the loss of the mechanical properties of the paper and its correlation with the methanol chemical marker.…”
Section: Introductionmentioning
confidence: 98%
“…Once the degradation has attained the LODP value, a downward curvature appears in the graphic, which could be explained by fewer methanol molecules produced once in the more stable crystalline region. Although a linear relationship exists between the generation of methanol and the concentration of broken bonds, the amount of methanol does not follow a 1:1 ratio with the concentration of chain-end groups, as demonstrated elsewhere (Jalbert et al 2007(Jalbert et al , 2015Gilbert et al 2008Gilbert et al , 2009). Since these experiments are performed without oil, methanol partition within the oil matrix is not responsible for its low production yield.…”
Section: Identification Of Pyrolysis Productsmentioning
confidence: 90%
“…For the first time, a linear relationship between the generated methanol and depolymerization of cellulose (rupture of 1,4-bglycosidic bonds) was established (Jalbert et al 2007). Later on, kinetic studies of the degradation of standard wood kraft and thermally upgraded insulating paper provided additional confirmation that methanol originates from the cellulose chopped-end chains (Gilbert et al 2008Jalbert et al 2015). New studies have confirmed the applicability of methanol as a new marker for paper degradation in power transformers (Schaut et al 2011;Jalbert et al 2012a) and an analytical methodology is available for the determination of these two alcohols in transformer oil, with detection limits in the low ng g -1 concentration level (Jalbert et al 2012b).…”
Section: Introductionmentioning
confidence: 96%